A Collaborative Story Writing Project Using Google Docs and Face-to-Face Collaboration - Wilson, Deirdre (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
The Google Docs application is part of Google Workspace for Education, a suite of cloud-based productivity and collaboration tools that are now ubiquitous in middle and high school classrooms. While there is an expanding body of research documenting the benefits of using Google Docs to support collaborative writing projects, there exists few qualitative studies detailing how cloud-based tools are integrated into courses that meet face-to-face on an ongoing basis. This case study explores how an experienced high school English teacher facilitated a collaborative writing project, in which students used Google Docs to co-write a story. The students were instructed to work on their stories asynchronously from home and synchronously during face-to-face classes. Data sources included field notes from class observations, reflections written by the teacher, semi-structured interviews with the teacher, focus group interviews with the students, and the shared Google Docs. This article describes affordances and constraints associated with the pedagogical supports provided during the collaborative writing process and offers recommendations for teachers who intend to use Google Docs to facilitate collaborative writing projects.